A hierarchical linear elastic boundary element solver for lenticular ore bodies - Zietsman, Christiaan Abraham (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Mathematical Sciences. Applied Mathematics))--University of Stellenbosch, 2007.